A Hermeneutic Study of Subjective Meanings in Mulla Jiziri’s Thought - Abdulrahman, Hussein O.; Mohamed, Mohamed B. (Humanities Journal of University of Zakho, 2014)
The study of hermontics has not been dealt with as a scientific approach to the applied studies of the Kurdish literature criticism so that the reader can understand texts in a new different way concerning the achievement of self-delight. In order to achieve the main purpose, one of Mulla Jiziri’s poems has been studied and analyzed hermontically to show the subjective view of the poet. This is a contribution to make the reader be able to have an exact idea about the poet’s thought and cerebration. Hence, the reader can have new dimensions in understanding the texts, approaching to the poet’s thinking more closely.